Ketogenic diet for ovarian disorders - promising nutritional approach in polycystic ovarian syndrome and ovarian cancer - Wojtuś, Magda; Tomaszuk, Sebastian; Wąsik, Karolina (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Polycystic ovary syndrome (PCOS) is the most common endocrine disease in the female reproductive age. As treatment guidelines include lifestyle changes, various diet types are being evaluated in terms of efficacy among them ketogenic diet (KD) which was also assessed in terms of its influence on another ovarian related disease - ovarian cancer. The aim of this paper is an analysis of the available scientific data in respect of the role of the KD as a part of the therapy of ovarian related disorders. The search was conducted using PubMed and Google Scholarship databases. Brief description of the state of knowledge: Ketogenic diet demonstrates favorable effects in the hormonal profile of PCOS-affected women. It was also noticed that its administration results in the reduction of BMI and the improvement in glycemic parameters. Most of the research was conducted by linking the ketogenic diet with the caloric restriction. In the matter of ovarian cancer the results are unclear; some of the research states the improvement of the quality of life of the participants, but there is some alarming data of the possible role of KD in enhancing the tumor growth. Conclusions: Ketogenic diet merits further research as a possible factor in the treatment of PCOS as foregoing results are pointing to its efficacy. Nevertheless, still more data is needed to determine its role as studies were conducted within a short period of time with relatively small research groups. There are also other limitations such as the lack of comparison with other dietary patterns with the caloric deficit which makes it difficult to deduce the main profitable factor. When it comes to ovarian cancer the results of the current data are also unclear and unambiguous with the possible negative effects.